Anti‐PF4 testing for vaccine‐induced immune thrombocytopenia and thrombosis and heparin induced thrombocytopenia: Results from a UK National External Quality Assessment Scheme exercise April 2021. (5th July 2021) - Reilly‐Stitt, Christopher; Kitchen, Steve; Jennings, Ian; Horner, Kevin; Jones, Robert; Makris, Mike; Walker, Isobel D.
Abstract: Background: Vaccine‐induced immune thrombocytopenia and thrombosis (VITT) following the administration of the AstraZeneca (AZ) ChAdOx1 nCOV‐19 vaccine has recently been reported. The associated clinical and laboratory features have included thrombosis at unusual sites, thrombocytopenia, and raised D‐dimers with positivity for IgG anti‐platelet factor 4 (PF4) antibodies. Objectives: A UK National External Quality Control Assessment Scheme external quality control exercise was carried out by distributing liquid and lyophilized samples from a subject with VITT, a pool of samples from subjects with classical heparin‐induced thrombocytopenia (HIT), and a non‐VITT/non‐HIT case to 85 centers performing HIT testing. Methods: Participating centers employed their locally validated testing methods for HIT assays. Results: The lyophilized and liquid samples were found to be commutable for the ELISA assays used in the detection of anti‐PF4 antibodies. The Aeskulisa, Stago, Hyphen, and LIFECODES anti‐PF4 ELISA assays successfully detected the VITT antibody, whereas the Acustar HIT, Werfen LIA, and the Stago STIC assays did not. Conclusion: It is important that clinical and laboratory teams are aware of the limitations of some anti‐PF4 assays when using them to aid diagnosis of VITT syndrome.